Effectiveness of Training Aids Used by KVK Trainers - Shobhana Gupta; K. L. Dangi (Indian Journal of Extension Education, 2013)
The present study is focused on effectiveness of training aids in acquiring knowledge, skill and attitude by farm-women of Rajasthan State. Information was collected from randomly selected 120 women farmers as well as 60 scientists from rd the III Agro Climatic Zone of the state using interview schedule. Analysis of data was carried out using frequency counts, percentages, means, weighted mean scores and correlation. A positive and significant relationship existed between effectiveness of training aids with age and level of education. Therefore, it becomes imperative that these significant determining factors to the effectiveness of the training aids in achieving the main tasks of extension service should be kept in mind before selecting any aid for extension trining programme.